ANALISIS HUBUNGAN KANDUNGAN TOTAL MOISTURE, TOTAL SULPHUR DAN ASH CONTENT TERHADAP GROSS CALORIFIC VALUE PADA BATUBARA - Anggreini, Dian; Bahtiar, Syamsul; Widyawati, Fauzi; Hidayat, Syamsul (Jurnal TAMBORA, 2021)
Most of the coal is used as fuel in power plants,cement industry and metal processing industry. Use of coal as fuelwill depend on the quality of the coal used. The main parameters thatdetermining the quality of coal is the calorific value. Meanwhile, the calorific value of a coalwill depend on several parameters, namely total moisture, total sulfur andash content. This study aims to determine the effect of the relationship betweenthe content of some of these parameters on the calorific value of a coal. Analysisperformed using the American Society for Testing and Materials (ASTM).The stages of this analysis include sample preparation, air dry loss testing, residualmoisture, total sulfur, ash content and gross calorific value. The results of the analysis showthat the higher the total moisture content, total sulfur and ash content, the higher thecauses the lower the calorific value of a coal.